Aboriginal Recommendations for Substance Use Intervention Programs - Nichols, Fiona (Aboriginal and Islander Health Worker Journal, 2010)
Objective: To identify Aboriginal people's perceptions of residential alcohol (and other drug) intervention programs. Method: Part of a wider Aboriginal-initiated study into Aboriginal perceptions of alcohol misuse and intervention, using adescriptive, grounded theory, participatory action design. Of 100 participants in individual and focus group interviews, only 22 people had personal or family experience of residential alcohol intervention programs. This paper presents the collated responses of this small group to qualitative, semistructured interview questions regarding their perceptions of intervention programs - and compares them to the literature and to the wider study's findings. Results: Positively evaluated components included 'time out', personal health gains, substance use education, life-skills training, support, socialising and - on dry communities - peace in 'country'. Criticisms focused largely on perceived long-term ineffectiveness, lack of skills development, culturally inappropriate environment and teaching style, accessibility to substances, separation from family, and staff skill/experience issues. Conclusions and Implications: Among the small group of remote area Aboriginal people participating in this aspect of the study, recommendations for substance misuse intervention programs suggested the need for programs significantly different from those generally available. In comparison with the substance-misuse orientation of many available intervention programs - and consistent with themes emerging in the literature and in other aspects of the wider study - participants' responses implied the need fora priority expansion of intervention focus onto the teaching and strengthening of skills required for self-determination. Co-operative inter-agency contributions to existing programs may be one means to achieving this.